Developmental disorders of the hip treated at the clinic for orthopaedic diseases in a period of 10 years(2009-2018) - Komnenovik M; Bozhinovski Z; Trajanovski A; Saveski A; Damjanovikj D; Atanasovski I (Институт за јавно здравје на Република Македонија = Institute of public health of Republic of Macedonia, 2022)
Developmental hip dysplasia includes a wide range of conditions such as subluxation, dislocation, hip instability, and teratological hip. The diagnosis was confirmed by clinical examination, ultrasound examination and anterior-posterior view radiograph (AP). Treatment varied depending on the patient's age and the degree of dysplasia: Pavlik harness, closed reduction, open reduction and corrective osteotomies. In this study 242 patients were included, of whom 198 were female patients and 44 male. All of the patients were treated with conservative treatment- closed reducation and spica casting. Left-sided dislocations were more common than right sided dislocations with predominance in the female patients. The main treatment in follow-up patients was closed reduction with or without adductor muscle tenotomy (m. add. longus). In cases with unsuccessful attempt of closed reduction, open reduction was performed with or without adductor muscle tenotomy. Depending on the residual dysplasia, patients were additionally treated with pelvic osteotomies (Salter 's inominate osteotomy), varus derotation osteotomy, valgus osteotomy, proximal femoral resection, and trochanter major transposition. 167 patients were treated with closed reduction and 3 with open reduction. The remaining patients were treated with closed reduction and additional surgery or with open reduction and additional surgery. Out of all treated patients, only 10 patients had recurrent dislocation of the hip, 7 female and 3 male patients. Closed reduction was performed again on two patients, and open reduction of the hip was performed on one patient. The average age of patients was 21.5 months. By presenting the cases in a period of 10 years, it was conclud that most cases were diagnosed later. Also, the standard closed reduction treatment was successful even after the first year in said patients. Depending on the residual dysplasia of the hip, in order to achieve better congruence of the joint, additional surgeries were performed.
Развојни нарушувања на колкот кои се третирани на клиниката за Ортопедски Болести во период од 10 години(2009-2018)